An investigation on compressive strength of cement mortar with seashell powder additive - Chua, Pei Shan (2014)
In order to improve performances of cement mortar and cost consideration, several alternatives have been selected. Among several of natural additives, seashells have been chosen. This is due to its high percentage of calcium carbonate which contributes to toughness property. Moreover, environmental pollution might occur if seashells are not properly disposed of. Hence, the potential of seashell powder as an additive for cement mortar has been investigated. The objectives of this research are to identify the best compressive strength of cement mortar with acceptable percentages of seashell powder, to determine modification of modulus elasticity of cement mortar as well as to investigate the time to failure against force. A total of 30 cubes of cement mortar samples were prepared with 0%, 1%, 2%, 3% and 4% seashell powder additive. Cube specimens of 100mm x 100mm x 100mm were moulded and cured for 7th and 28th days. After that, the compressive strength of cement mortar samples with seashell powder additive was tested using Universal Tensile Machine. The results revealed that the compressive strength of cement mortar with 1% seashell powder additive is higher than control sample. In term of failure, the cement mortar with seashell powder additive obtained longer time to failure compared to control sample. In general, seashell powder has potential become partially substitution of cement and improve performances of cement mortar.